Economic Status and Old-Age Health in Poverty-Stricken Myanmar - TEERAWICHITCHAINAN, Bussarawan (Institutional Knowledge at Singapore Management University, 2015)
Objective: We examine the association between poverty, economic inequality, and health among elderly in Myanmar. Method: We analyze 2012 data from Myanmar’s first representative survey of older adults to investigate how health indicators vary across wealth quintiles as measured by household possessions and housing quality. Results: Poverty and poor health are pervasive. Self-assessed health, sensory impairment, and functional limitation consistently improve with higher wealth levels regardless of socio-demographic controls. Differentials in self-rated health and sensory impairment between the bottom and second quintiles are clearly evident, suggesting that relative economic inequality matters even among very poor elders and that a small difference in wealth can matter in an extreme poverty setting. Discussion: Findings support a global theory of economic gradients in health regardless of level of societal poverty. Modest efforts to improve the standard of living among elderly may improve not only their material well-being but also their health.